An investigation into the interaction between water deficit and injury of sugarcane borer (Lepidoptera: Crambidae) in the gas exchange parameters and spectral reflectance of sugarcane - Soares, João Rafael Silva; Cesarin, Vinicius; da Rocha, Claudiane Martins; Mercês, Júlia Karoline; Watanabe, Fernanda Sayuri Yoshino; Imai, Nilton Nobuhiro; Tommaselli, Antonio Maria Garcia; Gratão, Priscila Lupino; Fernandes, Odair Aparecido (Journal of the science of food and agriculture, 2025)
Plants are subject to a variety of stressors that will eventually limit their development and yield. However, analysis of the combination of abiotic and biotic stresses is usually disregarded. The combination of stresses can have synergistic or antagonistic effects and, therefore, they require greater clarification for assertive decision-making. In this study, we examined how the interaction between water stress and sugarcane borer injury alters the physiological aspects of sugarcane through gas exchange parameters and foliar reflectance. Our results show that both stressors alter sugarcane physiology, but it is not possible to distinguish between the effects of sugarcane borer injury and those caused by water deficit based on the methodology adopted. Stresses, whether isolated or combined, disrupt gas exchange parameters, regardless of the post-infestation period and sugarcane variety. Among the differences that affect the combination of stressors are transpiration, stomatal conductance, and CO assimilation. The intercellular CO concentration and water use efficiency presented a positive and negative relationship, respectively, with lesion size (gallery length). The spectral response of sugarcane plants was similar regardless of treatments, with low classification metrics from machine learning models. The interaction between water stress and sugarcane borer injury alters key physiological traits in sugarcane, although their individual effects could not be fully distinguished. The knowledge generated from this study supports the possibility of refining the economic thresholds for the sugarcane borer in sugarcane since changes in sugarcane tolerance imposed by water restrictions can alter the current threshold applied. © 2025 The Author(s). Journal of the Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.